THE CORRELATION BETWEEN LISTENING AND SPEAKING AMONG HIGH SCHOOL STUDENTS - Yune Andryani Pinem (Universitas PGRI Yogyakarta, 2014)
This research looks at listening as one factor that gives contribution toward speaking among high school students. The study attempts to reveal through data analysis, in the form of students. score from each variable that both have correlation. Further the objective of the study is also to find out the extent of influence contributed by listening toward speaking. The research applies library study and field study (instrument designing and test performing both for listening and speaking). The theory used for analysis deals with listening and speaking correlation from language learning review. The result of the study demonstrates that the correlation of listening as the independent variable with speaking as dependent variable is positive. It also proves that with a unit of program or treatment given toward listening class, there will be a significant improvement equals with 3.134 times from previous speaking score for the same sample. For the analysis of data, the extent of correlation between two varibales is shown as low. It indicates that even though listening do have positive correlation towarde speaking, it is not the only deminant factor to determine success in speaking.